2021
DOI: 10.1177/19485506211043681
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Term and Longer Term Immigration Trends on Voting for Populist Radical Right Parties in Europe

Abstract: The success of populist radical right parties (PRRPs) in Europe has, in part, been attributed to growing immigration, but previous findings have found an inconsistent relationship between immigration and voting for PRRPs. We address previous inconsistencies by suggesting a time-focused perspective on intergroup relations. We disentangle short-term from longer term immigration trends and argue that a recent increase in immigration should predict PRRP support. With time, however, citizens will adapt to these dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…In line with previous studies, we found that two critical conditions fueled threat reactions: narratives about the impending minority position of the ethnic-racial majority group and rapid growth in diversity (6,7,(11)(12)(13). We also found that even under these critical conditions, inclusive immigrant integration policies attenuated or completely buffered ethnic-racial majorities' threat reactions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous studies, we found that two critical conditions fueled threat reactions: narratives about the impending minority position of the ethnic-racial majority group and rapid growth in diversity (6,7,(11)(12)(13). We also found that even under these critical conditions, inclusive immigrant integration policies attenuated or completely buffered ethnic-racial majorities' threat reactions.…”
Section: Discussionsupporting
confidence: 89%
“…A robust line of experimental research shows how narratives highlighting that in the future, ethnic-racial majorities will become numerical minorities provoke threat reactions (7,9,10). The second condition involves rapid growth in ethnic-racial diversity, bolstered by converging evidence from three large-scale multinational surveys (11)(12)(13). Together, it appears that there are critical conditions, such as prevailing narratives about losing one's majority position or rapid increases in diversity, that are especially likely to provoke threat reactions among ethnic-racial majorities.…”
Section: Introductionmentioning
confidence: 99%